2023
DOI: 10.1101/2023.02.04.527142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The representational geometry of cognitive maps under dynamic cognitive control

Abstract: Recent work has shown that abstract, non-spatial relationships between entities or task states are organized into representations called cognitive maps. Here we investigated how cognitive control enables flexible top-down selection of goal-relevant information from multidimensional cognitive maps retrieved from memory. We examined the relationship between cognitive control and representational geometry by conducting parallel analyses of fMRI data and recurrent neural network (RNN) models trained to perform the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…However, much of our social learning outside the lab occurs with respect to some underlying motivation (e.g. making friends, getting a job, seeking information) and several studies have demonstrated how task or goal relevant constraints change how cognitive maps are constructed (Park et al, 2023;Wilson et al, 2014). A promising direction for future work is examining how learning, representation, and memory of people and their relationships changes as a function of such goals.…”
Section: Discussionmentioning
confidence: 99%
“…However, much of our social learning outside the lab occurs with respect to some underlying motivation (e.g. making friends, getting a job, seeking information) and several studies have demonstrated how task or goal relevant constraints change how cognitive maps are constructed (Park et al, 2023;Wilson et al, 2014). A promising direction for future work is examining how learning, representation, and memory of people and their relationships changes as a function of such goals.…”
Section: Discussionmentioning
confidence: 99%